1997
DOI: 10.1002/j.1556-6676.1997.tb02331.x
|View full text |Cite
|
Sign up to set email alerts
|

Refusal and Resistance Skills for Children and Adolescents: A Selected Review

Abstract: The authors review the literature on refusal and resistance skill (RRS) training implemented with children and adolescents. RRS training is critically evaluated across different target behaviors and outcomes. RRS efficacy is considered for tobacco use, includingE very year millions of dollars are provided to school systems across the United States to implement prevention and intervention programs, most of which are funded through the U.S. Department of Education (Dryfoos, 1993), the Department of Health and Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 57 publications
0
14
0
2
Order By: Relevance
“…Given the salient role of peers as youth transition into adolescence, greater consideration should be given to examining how peers affect decisions among youth to engage in risky behavior. It has been suggested that because peer acceptance is highly salient during adolescence, youth who are reliant on friends for validation of self-worth may be at greater risk [18]. Although moderate peer orientation is normative and helps adolescents to establish autonomy as they make the transition to adulthood [19], some youth become excessively peer oriented, to the extent that they abandon family values and personal strengths to gain popularity [20].…”
Section: Youth Mediatorsmentioning
confidence: 99%
“…Given the salient role of peers as youth transition into adolescence, greater consideration should be given to examining how peers affect decisions among youth to engage in risky behavior. It has been suggested that because peer acceptance is highly salient during adolescence, youth who are reliant on friends for validation of self-worth may be at greater risk [18]. Although moderate peer orientation is normative and helps adolescents to establish autonomy as they make the transition to adulthood [19], some youth become excessively peer oriented, to the extent that they abandon family values and personal strengths to gain popularity [20].…”
Section: Youth Mediatorsmentioning
confidence: 99%
“…Diversos estudos foram encontrados, com o foco nos programas preventivos ao uso de substâncias, baseados no treinamento de habilidades sociais de recusa e de resistência às drogas (Donohue, Van-Hasselt, Vincent, Hersen & Perrin, 1999;Herrmann & McWhirter, 1997;Rosenbaum & Hanson, 1998). Muitos consistem em programas integrantes do currículo escolar, desenvolvidos ao longo do ensino médio durante dois ou três anos (Botvin, 2000b;Hecht e cols., 2003;O'Hearn & Gatz, 2002;Payton, Wardlaw, Graczyk & Bloodworth, 2000).…”
Section: Habilidades Sociais Adolescentes E Maconhaunclassified
“…The substance use prevention literature identifies a number of social skills as crucial to the ability to deal with peer influences to use drugs (Botvin & Botvin, 1992;Hermann & McWhirter, 1997;Miller et al, 2000;Skara & Sussman, 2003). The teaching of decision-making and resistance skills plays a prominent role in effective prevention programs (Griffin, Botvin, Nichols, & Doyle, 2003;Hecht et al, 2003).…”
Section: Peer Influences Social Skills and Substance Usementioning
confidence: 96%